Maximising geotechnical data and characterisation of critical units through targeted field work - Phillips, AJ; Wilson, HF (Slope Stability 2013: Proceedings of the 2013 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2013)
Identification and investigation of weak geological units and structures is an important component of a slope design. Such units and structures are highly prone to weathering and typically exhibit lower shear strength than the surrounding rock mass. These units are inherently problematic to obtain quality geotechnical data from due to their fragile nature and often limited frequency. It is therefore essential that a data collection campaign is designed and implemented with the view of collecting maximum quality and representative data from these units. Samples with minimised disturbance from diamond drill core provide a valuable insight into the in situ ground conditions of these units. This method of data collection requires good quality drilling and early identification of weaker units to maximise recovery. Careful handling, correct sampling and transport procedures to enhance preservation of the core until geotechnical laboratory test work can be undertaken are equally essential. It should be ensured that samples are preserved in their in situ conditions prior to arrival at the testing laboratory. Consideration needs to be given to communication between all personnel, early identification of critical weak units, timing of logging and sampling and sample transportation and storage. This paper aims to provide a methodology for sampling of such materials, building on the knowledge of the current standards and best practice benchmarked with other industries. The ultimate result is the ability to collect and preserve a higher quantity and quality of samples of weak material critical to slope stability. With increased sampling from weaker units, it is possible to rely more on results of laboratory testing and reduce reliance on empirical methods for shear strength characterisation. This provides increased confidence in the geotechnical model and ultimately slope design.